Endoscopic-Assisted Linea Alba Reconstruction plus Mesh Augmentation for Treatment of Umbilical and/or Epigastric Hernias and Rectus Abdominis Diastasis – Early Results - Köckerling, Ferdinand; Botsinis, Marinos Damianos; Rohde, Christine; Reinpold, Wolfgang (Frontiers in Surgery, 2016)
Introduction Symptomatic umbilical and/or epigastric hernias are often seen concomitantly with rectus abdominis diastasis (RAD), and suture repair of such defects has a high recurrence rate. In the literature there are reports of both endoscopic and open techniques for repair of symptomatic umbilical and/or epigastric hernias in association with RAD. This paper now reports on the early results of a hybrid technique used for reconstruction of the linea alba and mesh augmentation (ELAR plus). Material and methods Between 15 June 2015 and 31 January 2016, 40 patients with symptomatic umbilical and /or epigastric hernia and concomitant RAD underwent reconstruction of the linea alba using a hybrid technique involving a small umbilical incision and the use of video endoscopic equipment. The patients comprised 29 men and 11 women with a mean age of 53.6 years and mean BMI of 32.6. The mean operating time was 120 minutes. The mesh had a mean longitudinal extension of 18.6 cm and transverse extension of 9.1 cm. Results Thirty-day follow-up results are available for all patients. Thirty-seven out of 40 patients (92.5 %) experienced no postoperative complication. Two cases of discrete impaired umbilical wound healing and one seroma were successfully managed with conservative treatment. On 30-day follow-up, three out of 40 patients (7.5 %) complained of intermittent pain on exertion, and two out of 40 patients (5 %) still took painkillers when required. Conclusion Endoscopic-assisted linea alba reconstruction plus mesh augmentation (ELAR plus) is a novel minimally invasive procedure for repair of symptomatic umbilical and/or epigastric hernias with concomitant RAD. Reconstruction of the linea alba via a minimally invasive access route is able to restore the normal anatomy of the abdominal wall.